Driven : how to make it in Philippine business ([Makati, Philippines] : Class 1971, Asian Institute of Management, 2004)
Graduates of the Asian Institute of Management, class of 1971, commemorate their 35th anniversary.
Being your own boss -- Being the boss -- Managing change -- Managing the future
Bautista, Francisco H., [editor];Samson, Antonio R., [editor];Zafra, Jessica, [editor]
Keywords: ASIAN INSTITUTE OF MANAGEMENT -- ALUMNI AND ALUMNAE